ANALISA CFD PENGARUH LOKASI PEMASANGAN FLOW STRAIGHTENER BESUDUT 450 TERHADAP PEMBACAAN FLOW METER - Pramadhony .; Muhammad Lazim; Muhammad Amin Fauzie; Togar P.O. Sianipar (Universitas Tridinanti Palembang, 2018)
A chemical plant needs some high accurate instrumentations in order to support an efficient production process. Flow meter, one of instrumentation types, has function to read the flow rate of a fluid. The error of reading in flow meter can cause some problems such as incorrect reaction doses and the error in the amount of product transferred to consumer. Flow meter installation has to fulfil some requirements in order to achieve an accurate measurement. The altering of flow direction can change the flow pattern and triggers a swirling flow which has to be avoided when it flows through flow meter. Generally flow meter is designed can be work well in an ideal condition. The requirements are a uniform velocity profile, free from a swirling flow and turbulence flow regime. A limitation of space sometimes causes a problem when installing flow meter in an ideal condition. A 45° inclination of flow straightener has better performance in eliminating the swirling flow and improving the velocity profile. By installing the flow straightener in various locations, the required fluid pattern can be obtained as closer as possible form the upstream. In this research, the authors conduct a CFD analysis to the flow of bio-diesell inside the pipe before it is read by flow meter. Keywords: : Flow Straightener, Swirling Flow, Flow Meter